Optical characterization of sol–gel ZnO:Al thin films. (September 2015) - Ivanova, T.; Harizanova, A.; Koutzarova, T.; Vertruyen, B.
Highlights: Sol–gel deposition of ZnO, ZnO:Al and Al2 O3 films. Structural evolution of ZnO:Al films as a function of aluminium concentration and annealing temperature (from 500 to 800 °C). ZnO:Al films reveal deterioration of film crystallization compared with single ZnO films. Transmission of the ZnO:Al films is reaching 90% in visible region with increasing Al component. Abstract: This work presents a sol–gel approach for ZnO:Al films deposition. The effect of Al component and annealing treatments (from 500 to 800 °C) on the film structural and optical properties has been studied. Sol–gel ZnO and Al2 O3 films are used for comparative analyses. Structural evolution as a function of annealing temperatures is investigated by using X-ray diffraction (XRD). XRD analysis of ZnO:Al films revealed that the predominant crystal phase is a wurtzite ZnO. It can be seen that the addition of Al leads to decaying of the film crystallinity. Fourier Transform Infrared (FTIR) and UV–VIS spectrophotometry are applied for characterization of the vibrational and optical properties. The Al component influences the shapes of the absorption bands. The optical properties of the sol–gel ZnO, ZnO:Al and Al2 O3 films reveal very interesting features. Increasing Al component results in significantly higher film transparency.